8A.007 Evaluating the impact of a road safety education project in Madagascar schools. (14th March 2021) - Perego, Paolo; Biassoni, Federica; Silva, Ana Luisa; Clark, Sam; Randrianarisoa, Jesse
Abstract : Context: Road crashes are the leading cause of death for children and young adults aged 5–29 worldwide. Education is an important part of a safe systems approach to improve road safety. However, evaluating the effectiveness of road safety education projects is challenging. This presentation shares the experience of a quasi-experimental approach to assess the impact of an NGO project implemented in six primary schools in Antananarivo, Madagascar, between 2017–2018. Analysis: The project evaluation was conducted in August 2019. Photos showing nine Malagasy road crossing scenarios were presented to students in random order. Students should consider that they were in the perspective of the person who took the photo and wanted to cross the road. They must therefore indicate the areas of the photo where they would look at first, at second and third. Outcomes: Data was analyzed for two samples: 250 students from project participant schools and 300 students from other schools in the same city. The number of students able to apply the correct rules for different road crossing scenarios (look first left, second right and left again before crossing) was on average 20% higher in project participant schools. Learning Outcomes: The results of this impact assessment, combined with a separate teacher evaluation, will contribute to a revision of the techniques used by the NGO to build teacher capacity and to teach students to correctly apply the rules when facing a real situation. The methodology is a cost-effective tool to evaluate the impact of road safety education in schools.